THE EFFECT OF USING OPEN-ENDED ORAL QUESTIONS ON THE ACADEMIC ACHIEVEMENT OF PHYSICS FOR FOURTHGRADE STUDENTS AND THEIR CREATIVE THINKING - Sameerah Adnan Thrther (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The current research aims to identify (the effect of open-ended oral questions on achievement and creative thinking) for the academic year (2019-2020) for students of the fourth grade of science at Fatima Al-Zahra High School for Girls in Anbar Governorate. It consisted of (50) items of a multiple-type test, and theresearchers adopted the two researcher’s creative thinking test (Khairallah, 1975). The results of the study showed the superiority of the experimental group over the control group in achievement and creative thinking. In light of these results, the researcher recommended that physics teachers should pay attention to open-ended oral questions and limit the use of closed-ended oral questions.